Fe / Ni-SiC-Fe3Si wood-structure wave-absorbing material with industrial-agricultural solid waste resources as raw materials and preparation method of Fe / Ni-SiC-Fe3Si wood-structure wave-absorbing material

By using solid waste resources such as iron tailings, red mud and corn cob core, wet ball milling and microwave reaction technology are used to prepare Fe/Ni-SiC-Fe3Si absorbing materials, solving the problem of complex and high cost of silicon carbide material preparation process , realizes efficient utilization of solid waste resources and improves wave absorption performance, and reduces environmental pollution and resource waste.

CN119263285APending Publication Date: 2025-01-07SHENYANG LIGONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204554.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The preparation process of existing silicon carbide absorbing materials is complex and costly, making it difficult to achieve doping modification and multi-dimensional structural composite, and the utilization rate of industrial and agricultural solid waste resources is low, resulting in environmental pollution and resource waste.

Method used

Using industrial solid waste resources iron tailings, red mud and agricultural solid waste resources corn cob core, Fe/Ni-SiC-Fe3Si wooden structure absorbing materials are prepared through wet ball milling and microwave reaction technology, achieving high value of solid waste resources Chemical utilization and multi-dimensional structural composite.

Benefits of technology

It reduces the preparation cost, simplifies the process, improves the wave absorption performance, and realizes the efficient utilization of solid waste resources. It has important theoretical significance and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263285A_ABST
    Figure CN119263285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wave-absorbing ceramic materials and preparation, and discloses a Fe / Ni-SiC-Fe3Si wood structure wave-absorbing material with industrial-agricultural solid waste resources as raw materials and a preparation method of the Fe / Ni-SiC-Fe3Si wood structure wave-absorbing material. Preparing solid waste-based slurry; infiltrating corn cobs in the solid waste-based slurry, taking out and drying the corn cobs, and putting the corn cobs into a microwave reaction furnace for microwave heating to obtain a carbonized corn cob precursor; placing a graphite crucible in a sintering furnace, placing the graphite crucible at the bottom of the graphite crucible, placing the carbonized corn cob core precursor at an opening in the upper part of the graphite crucible, covering the graphite crucible with a graphite cover, and performing carbonization reaction firing to obtain the Fe-SiC wood structure wave-absorbing material. According to the method, an industrial solid waste resource is used as a Fe source, an agricultural solid waste resource is used as a C source, and the Fe3Si compounded and Fe / Ni doped silicon carbide composite wave-absorbing material is prepared through an in-situ carbon thermal reduction process on the premise that the original rich anisotropic microstructure of a wood material is reserved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microwave-absorbing ceramic materials and preparation technology, and in particular to a Fe / Ni-SiC-Fe3Si wood structure microwave-absorbing material using "industrial-agricultural" solid waste resources as raw materials and a preparation method thereof. Background Art

[0002] With the popularization of wireless communication technology, electromagnetic interference caused by electromagnetic radiation will not only directly affect the normal operation of electronic equipment and the safety of information transmission, but high-frequency electromagnetic radiation will also have a serious impact on human health and embryonic development. Through structural design and regulation, the development and application of absorbing materials that can absorb electromagnetic waves efficiently and effectively is one of the effective solutions to reduce and eliminate electromagnetic pollution and electromagnetic interference.

[0003] Silicon carbide has good wave absorption performance. It is a wide bandgap semiconductor with high saturated electron mobility and high thermal conductivity. It can be used in a variety of high-power, high-frequency electronic devices, especially high-temperature components. Compared with other absorbing materials, silicon carbide has the advantages of high high-temperature wave absorption performance and dielectric properties that can be adjusted by doping modification, which can achieve light weight, thin layer, and wide-band absorption. Since the dielectric properties of silicon carbide are quite different from those of air, the wave absorption performance of pure silicon carbide in the microwave frequency band is not outstanding. In order to improve the wave absorption performance of silicon carbide materials, silicon carbide needs to be processed. Generally speaking, there are two methods: doping modification and forming a silicon carbide composite material with a multi-dimensional microstructure.

[0004] Natural plants often contain rich long-range continuous directional pore structures, which can be used as templates to prepare multi-dimensional wood-structured silicon carbide materials with fine grading. The common preparation methods currently include template replacement technology and sol-gel high-temperature reaction technology, but both have high production costs and complex processes, and require subsequent processes for doping and modification. However, the wood-structured silicon carbide materials formed by them are often of low purity and poor tissue heredity, which seriously affects the performance and application of silicon carbide materials.

[0005] The preparation process of silicon carbide is relatively complicated and costly. How to achieve doping modification and multi-dimensional structural composite of silicon carbide while reducing costs is one of the current research difficulties in the preparation of silicon carbide absorbing materials.

[0006] As the world's largest agricultural and industrial producer, my country generates a huge amount of industrial and agricultural waste every year. The collection and transportation of agricultural solid waste resources takes a long time and requires a lot of work. In addition, there is usually open-air burning of waste, which causes air pollution. The accumulation of solid waste will damage the soil structure of farmland and even affect surface runoff and groundwater, causing water pollution and harming people's lives. In industrial production, due to the differences in the characteristics of mineral resources and the limitations of production technology, low-grade mineral recycling rates, difficulties in recycling valuable components, and large-scale storage of surrounding rocks, waste rocks, and tailings often result, which not only occupy land, but also cause serious pollution to the environment. Traditional utilization methods have problems such as low utilization rate and high production cost, and they focus on directly producing low-value-added extensive products, resulting in a huge waste of resources.

[0007] Industrial solid waste resources such as iron tailings, red mud, and magnesium slag contain a certain amount of Fe and a small amount of Ni, while corn cob cores are natural porous structural materials. Both provide the necessary material basis for the preparation of silicon carbide with doping modification and multi-dimensional pore structure. Therefore, aiming at cutting-edge new materials and their key preparation technologies, conducting key technology research on the coordinated, efficient, and high-value utilization of various solid waste resources, and developing materials with high added value, it is expected that while absorbing industrial / agricultural solid waste resources such as iron tailings, red mud, magnesium slag, and corn cob cores, the comprehensive utilization rate will be improved, bringing ideal economic returns and technical support for mining development and rural revitalization. Summary of the invention

[0008] The present invention uses industrial solid waste resources such as iron tailings, red mud, magnesium slag and natural wood material corn cob core as raw materials, uses dark minerals rich in iron tailings, red mud and magnesium slag as Fe sources, and uses corn cob core as carbon source. Under the premise of retaining the original rich heterogeneous microstructure of wood materials, the iron-doped silicon carbide composite absorbing material is prepared, which not only greatly reduces the reaction cost, but also realizes the high-value utilization of solid waste resources, and has important theoretical significance and economic value. The present invention belongs to the field of comprehensive utilization of mineral resources and absorbing materials, and proposes a method of processing and high-value utilization of "industrial-agricultural" solid waste resources to prepare Fe / Ni-SiC-Fe3Si ceramic absorbing materials with wood structure.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] A method for preparing a Fe / Ni-SiC-Fe3Si wood structure absorbing material using "industrial-agricultural" solid waste resources as raw materials comprises the following steps:

[0011] Step (1), preparing a solid waste-based slurry;

[0012] The raw material components of the solid waste-based slurry are as follows: 30-50 parts of red mud, 20-30 parts of any one of iron tailings and magnesium slag or any combination thereof in any proportion;

[0013] The raw materials are mixed by weight, 180-200 parts of water are added, wet ball milled for 5-6 hours, screened and dried after grinding, and then 20-30 parts of carboxymethyl cellulose are added and stirred evenly, and adjusted to 25-35 degrees Baume to prepare a solid waste-based slurry;

[0014] Step (2), soaking the corn cob cob in the solid waste-based slurry for 5-10 minutes, taking it out for freeze-drying, and then putting it into a microwave reaction furnace, heating it to 280-320° C. at a rate of 3-5° C. / min, keeping it warm for 3-6 hours, and then cooling it naturally to obtain a carbonized corn cob cob precursor with a porous wood structure;

[0015] Step (3), placing a graphite crucible in a sintering furnace, taking 50-100 parts of SiO and placing them at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover, performing carbonization reaction and firing, and obtaining a wood structure absorbing material.

[0016] In the step (1), the ball milling speed is 50 rpm; the ball milling product is dried by placing it in a drying oven at 60-70° C. for 3-5 hours.

[0017] In the step (2), the freeze-drying time is 10-15 hours, and the microwave reaction furnace is preheated at 20-40° C. for 1-2 minutes before heating.

[0018] In the step (3), the specific heating process of the carbonization reaction firing is: from room temperature to 850-900°C at a heating rate of 13-15°C / min, then to 1500-1800°C at a heating rate of 1-3°C / min, keep warm for 3-5h, cool to 1000-1100°C at a rate of 2-4°C / min, keep warm for 1-1.5h, and then cool to room temperature.

[0019] In the steps (2) and (3), the firing process is carried out under a nitrogen atmosphere.

[0020] The Fe / Ni-SiC-Fe3Si wood structure absorbing material prepared according to the preparation method has a gray tone as a whole and has the original porous wood structure of a corn cob core.

[0021] In the present invention, a method for preparing a wood structure absorbing material suitable for solid waste resources is designed in consideration of the form and composition of solid waste resources. Iron-rich high dielectric constant minerals such as hematite, magnetite, siderite, biotite, and iron-poor low dielectric constant minerals such as plagioclase, hornblende, and quartz in iron tailings, red mud, and magnesium slag are wrapped and attached to the surface of corn cob wood fiber through slurry infiltration, and each mineral phase forms a mesh structure mineral film with fine pores on the surface of corn cob wood fiber through freeze drying; during the microwave process, the corn cob wood fiber is carbonized to black, and at the same time, the high dielectric constant minerals in the surface mineral film are rapidly heated during the microwave heating process, and the edges of the mineral particles are locally melted, connecting and solidifying the surrounding low dielectric constant minerals to form a shell layer.

[0022] During the reduction reaction firing process, silicon monoxide sublimates and passes through the mesh structure shell layer with fine channels to form the following reaction with the carbonized corn cob wood fiber:

[0023] 2C(s)+SiO(g)→SiC(s)+CO(g) (Reaction 1)

[0024] The carbonized corn cob wood fiber reacts with silicon monoxide to form silicon carbide and carbon monoxide, and the corn cob turns gray. At the same time, carbon monoxide and silicon monoxide reduce the iron-containing mineral shell on the fiber surface, forming the following reaction:

[0025] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 2)

[0026] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 3)

[0027] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 4)

[0028] Fe3Si and elemental iron and nickel are precipitated, and part of the iron and nickel elements are doped into silicon carbide during the high temperature process, and finally a Fe / Ni-SiC-Fe3Si composite absorbing material with an oxide shell and a wood fiber structure and composite doping is formed.

[0029] Beneficial effects of the present invention: The present invention uses dark minerals rich in industrial solid waste resources - iron tailings, red mud, and magnesium slag as Fe sources, and uses agricultural solid waste resources - corn cob cores as C sources. Through an in-situ carbon thermal reduction process, the present invention prepares Fe3Si composite, Fe / Ni-doped silicon carbide composite absorbing materials while retaining the original rich heterogeneous microstructure of the wood material. This not only greatly reduces the reaction cost and simplifies the process, but also realizes the high-value utilization of solid waste resources, which has important theoretical significance and economic value. The present invention provides new ideas and practical significance for the processing and utilization of solid waste resources in the field of advanced materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 and Figure 2 This is the microstructure diagram prepared in Example 1.

[0031] Figure 3 This is the EDS spectrum analysis diagram prepared in Example 1.

[0032] Figure 4 This is a diagram of the wave absorption performance prepared in Example 1.

[0033] Figure 5 XRD diagrams of material phases at different reduction firing temperatures. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with embodiments.

[0035] In the following embodiments:

[0036] The body is a porcelain body or a pottery body;

[0037] The iron tailings were taken from the tailings pond of the magnetite quartzite iron ore deposit in Liaoning; the red mud was taken from the Bayer red mud in the yard of an aluminum plant in Liaoning; and the magnesium slag was taken from a magnesium company in Liaoning.

[0038]

[0039] The red mud is mainly composed of cancrinite, calcite, hematite, magnesite, and tremolite; the iron tailings are mainly composed of quartz and hematite, with a small amount of magnetite, siderite, and tremolite; the magnesium slag is mainly composed of dolomite, ferrosilicon, and fluorite. A method for preparing a Fe / Ni-SiC-Fe3Si wood structure absorbing material using "industrial-agricultural" solid waste resources and corn cobs as raw materials, comprising the following steps:

[0040] Step (1), preparing a solid waste-based slurry;

[0041] The raw material components of the solid waste-based slurry are in the following weight ratios: 30-50 parts of red mud, 20-30 parts of any one of iron tailings or magnesium slag or a combination of the two;

[0042] The raw materials are mixed by weight, 180-200 parts of water are added, wet ball milled for 5-6 hours, screened and dried after grinding, and then 20-30 parts of carboxymethyl cellulose are added and stirred evenly, and adjusted to 25-35 degrees Baume to prepare a solid waste-based slurry;

[0043] Step (2), soaking the corn cob cob in the solid waste-based slurry for 5-10 minutes, taking it out for freeze-drying, and then putting it into a microwave reaction furnace, heating it to 280-320° C. at a rate of 3-5° C. / min, keeping it warm for 3-6 hours, and then cooling it naturally to obtain a carbonized corn cob cob precursor with a porous wood structure;

[0044] Step (3), placing a graphite crucible in a sintering furnace, taking 50-100 parts of SiO and placing them at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover, performing carbonization reaction and firing, and obtaining a wood structure absorbing material.

[0045] The freeze drying time is 10-15 hours, and the microwave reaction furnace is preheated at 20-40°C for 1-2 minutes before heating. The specific heating process of the reduction reaction firing is: from room temperature to 850-900°C at a heating rate of 13-15°C / min, then to 1500-1800°C at a heating rate of 1-3°C / min, keep warm for 3-5 hours, cool to 1000-1100°C at a rate of 2-4°C / min, keep warm for 1-1.5 hours, and then cool to room temperature.

[0046] Example 1

[0047] The method for preparing Fe / Ni-SiC-Fe3Si wood structure absorbing material comprises the following steps:

[0048] Step (1) preparing a red mud-magnesium slag-based slurry, wherein the raw materials of the red mud-magnesium slag-based slurry include components in a weight ratio of: 45 parts of red mud and 30 parts of magnesium slag;

[0049] The red mud and magnesium slag in the above raw materials are added with 190 parts of water according to the proportion of ingredients, and wet ball milled for 6 hours at a ball mill speed of 50 rpm. After grinding, the mixture is passed through a 300-mesh sieve and placed in a drying oven to dry at 70° C. for 5 hours. Then, 25 parts of carboxymethyl cellulose are added and stirred evenly, and the mixture is adjusted to 35 degrees Baume to obtain a red mud-magnesium slag-based slurry for standby use.

[0050] Step (2) soaking the corn cob in the red mud-magnesium slag-based slurry for 10 minutes, taking out and freeze-drying for 13 hours, and then putting it into a microwave reaction furnace preheated at 40° C. for 2 minutes, heating the temperature to 300° C. at a rate of 4° C. / min, keeping the temperature for 5 hours, and then cooling naturally to obtain a carbonized corn cob precursor with a porous wood structure, which is set aside;

[0051] Step (3) placing a graphite crucible in a sintering furnace, taking 80 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0052] The sintering furnace was heated from room temperature to 870°C at a heating rate of 14°C / min in a nitrogen atmosphere, then to 1700°C at a heating rate of 2°C / min, kept at that temperature for 4 h, cooled to 1050°C at a rate of 3°C / min, kept at that temperature for 1.5 h, and then cooled to room temperature to obtain the target product.

[0053] Through the freeze-drying process, the mineral phases in the slurry form a mesh-structured mineral film with fine pores on the surface of the corn cob wood fiber. During the microwave heating process, the iron-rich high dielectric constant minerals heat up and expand and partially melt at the edge of the particles. The mesh structure prevents the mineral film from deforming and falling off due to the increase in the volume of the mineral particles. At the same time, it also allows gaseous SiO to react with the carbonized corn cob during the reduction reaction. During the reduction reaction firing process, silicon monoxide sublimates and passes through the mesh-structured shell with fine pores to form the following reaction with the carbonized corn cob wood fiber:

[0054] 2C(s)+SiO(g)→SiC(s)+CO(g) (Reaction 1)

[0055] Corn cob core is fully carbonized and reduced under suitable temperature conditions (reaction 1) to form silicon carbide with a multi-dimensional wood fiber structure. Fe-rich minerals in the red mud-magnesium slag-based slurry adhere to the surface of wood fibers. The appropriate amount of SiO added, sintering temperature and insulation time during the carbonization reaction enable the mineral particles attached to the surface of wood fibers to be fully reduced. Iron-containing mineral phases such as hematite are reduced and precipitated on the surface of silicon carbide to form a dispersed Fe3Si shell layer (reactions 2 and 3).

[0056] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 2)

[0057] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 3)

[0058] Part of the iron-containing mineral phase is fully reduced to form iron and nickel elements precipitated on the surface of silicon carbide, and part of it is incorporated into silicon carbide in a high temperature environment (reaction 4).

[0059] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 4)

[0060] During the reduction reaction, due to the reaction of the bridging phase, the iron-poor low dielectric constant minerals lost their connection and fell off. The prepared Fe / Ni-SiC-Fe3Si wood structure absorber material was gray, and the overall wood fiber structure was maintained ( Figure 1 , 2 ) and has a Fe3Si shell on the surface. EDS spectrum analysis shows that metals such as Fe and Ni are precipitated on the surface of silicon carbide ( Figure 3 ), the wave absorption performance is as follows Figure 4 Shown as black line a.

[0061] Example 2

[0062] The method for preparing SiC-Fe3Si-Fe / Ni wood structure absorbing material comprises the following steps:

[0063] Step (1) a multi-source solid waste-based slurry, wherein the raw material components of the multi-source solid waste-based slurry are in the following weight ratio: 30 parts of red mud, 10 parts of magnesium slag, and 10 parts of iron tailings;

[0064] The solid waste in the above raw materials is added with 180 parts of water according to the proportion of ingredients, wet ball milled for 5 hours, the ball mill speed is 50 rpm, after grinding, it is passed through a 300-mesh sieve and placed in a drying oven to dry at 60-70°C for 3-5 hours, then 20 parts of carboxymethyl cellulose is added and stirred evenly, and adjusted to 25 degrees Baume to prepare a multi-source solid waste-based slurry for standby use;

[0065] Step (2) soaking the corn cob cob in the multi-source solid waste-based slurry for 5 minutes, taking it out and freeze-drying it for 10 hours, then putting it into a microwave reaction furnace preheated at 20° C. for 1 minute, heating it to 280° C. at a rate of 3° C. / min, keeping it warm for 3 hours, and then cooling it naturally to obtain a carbonized corn cob cob precursor for later use;

[0066] Step (3) placing a graphite crucible in a sintering furnace, taking 50 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0067] The sintering furnace was heated from room temperature to 850°C at a heating rate of 13°C / min in a nitrogen atmosphere, then to 1500°C at a heating rate of 1°C / min, kept at that temperature for 3 h, cooled to 1000°C at a rate of 2°C / min, kept at that temperature for 1 h, and then cooled to room temperature to obtain the target product.

[0068] 2C(s)+SiO(g)→SiC(s)+CO(g) (Reaction 1)

[0069] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 2)

[0070] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 3)

[0071] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 4)

[0072] Reaction 1 generates wood fiber structured silicon carbide, but due to the low concentration of multi-source solid waste-based slurry and the short impregnation time, there are fewer mineral particles attached to the surface of corn cob core wood fiber. In addition, the microwave time is short, and the consolidation degree of mineral particles attached to the surface of wood fiber is poor. The small amount of SiO added, the low sintering temperature and the insulation time during the carbonization reaction limit the reduction degree of mineral particles attached to the surface of wood fiber. Reaction 2, 3, and 4 are insufficient, and the Fe3Si and iron content of the reduced precipitation on the surface of silicon carbide formed are small, and the overall absorption efficiency is low.

[0073] Comparative Example 1

[0074] Step (1) preparing a red mud-based slurry, wherein the red mud-based slurry comprises components in a weight ratio of 100 parts of red mud;

[0075] The red mud in the above raw materials is added with 180 parts of water according to the proportion of ingredients, wet ball milled for 5 hours, the ball mill speed is 50 rpm, after grinding, it is passed through a 300 mesh sieve and placed in a drying oven to dry at 60-70° C. for 3-5 hours, then 30 parts of carboxymethyl cellulose is added and stirred evenly, and adjusted to 25 degrees Baume to prepare a red mud-based slurry for standby use;

[0076] Step (2) soaking the corn cob in the red mud-based slurry for 15 minutes, taking out and drying, and then placing in a microwave reaction furnace preheated at 20° C. for 1 minute, heating to 300° C. at a rate of 4° C. / min, keeping the temperature for 5 hours, and then cooling naturally to obtain a carbonized corn cob precursor for standby use;

[0077] Step (3) placing a graphite crucible in a sintering furnace, taking 70 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0078] Step (4) The sintering furnace is heated from room temperature to 850°C at a heating rate of 13°C / min in a nitrogen atmosphere, then heated to 1500°C at a heating rate of 1°C / min, kept at that temperature for 3 h, cooled to 1000°C at a rate of 2°C / min, kept at that temperature for 1 h, and then cooled to room temperature to obtain the target product.

[0079] 2C(s)+SiO(g)→SiC(s)+CO(g) (Reaction 1)

[0080] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 2)

[0081] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 3)

[0082] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 4)

[0083] The excessively high concentration and soaking time of the red mud-based slurry resulted in too many mineral particles attached to the surface of the wood fiber of the corn cob core. After the corn cob core was soaked in the red mud-based slurry, it was dried by the drying method. The mineral phase in the slurry was densely and evenly covered on the surface of the carbonized corn cob core to form a mineral film lacking a sufficient pore structure, and in the subsequent reduction reaction, it prevented the gaseous SiO from fully reacting with the corn cob core, resulting in incomplete reaction 1 and incomplete conversion of the wood fiber into silicon carbide. Therefore, the expected SiC-Fe3Si-Fe / Ni wood structure absorbing material could not be formed, and the absorbing performance was as follows Figure 4 Shown as black line b.

[0084] Comparative Example 2

[0085] Step (1) preparing a red mud-magnesium slag-based slurry, wherein the raw materials of the red mud-magnesium slag-based slurry include components in a weight ratio of: 45 parts of red mud and 30 parts of magnesium slag;

[0086] The red mud and magnesium slag in the above raw materials are added with 190 parts of water according to the proportion of ingredients, and wet ball milled for 6 hours at a ball mill speed of 50 rpm. After grinding, the mixture is passed through a 300-mesh sieve and placed in a drying oven to dry at 70° C. for 5 hours. Then, 25 parts of carboxymethyl cellulose are added and stirred evenly, and the mixture is adjusted to 35 degrees Baume to obtain a red mud-magnesium slag-based slurry for standby use.

[0087] Step (2) soaking the corn cob in the red mud-magnesium slag-based slurry for 10 minutes, taking out and freeze-drying for 13 hours, and then putting it into a microwave reaction furnace preheated at 40° C. for 2 minutes, heating the temperature to 300° C. at a rate of 4° C. / min, keeping the temperature for 5 hours, and then cooling naturally to obtain a carbonized corn cob precursor with a porous wood structure, which is set aside;

[0088] Step (3) placing a graphite crucible in a sintering furnace, taking 80 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0089] The sintering furnace was heated from room temperature to 870°C at a heating rate of 14°C / min in a nitrogen atmosphere, then to 1400°C at a heating rate of 2°C / min, kept at that temperature for 4h, cooled to 1050°C at a heating rate of 3°C / min, and kept at that temperature for 1.5h.

[0090] During the reduction reaction, the sintering temperature has an important influence on the formation of SiC. Increasing the synthesis temperature can promote the reduction reaction and is conducive to the formation of SiC phase. At 1350℃, some SiC has been generated. When the temperature rises to 1400℃, the SiC diffraction peak is significantly enhanced, but some impurity phases still exist in the product. When the temperature reaches 1500℃, the SiC diffraction peak continues to enhance, and the purity of the product SiC phase increases ( Figure 5 ). In this example, the reduction reaction temperature is low, resulting in incomplete conversion of carbonized corncob core into silicon carbide, with more residual carbon, lower purity and poor structural stability, and the expected wave absorption effect cannot be achieved. The wave absorption performance is as follows Figure 4 Shown as black line c.

[0091] Comparative Example 3

[0092] Step (1) preparing a FeCl3 / NiCl or Fe(NO3)3 / NiNO3-based slurry, wherein the FeCl3 / NiCl or Fe(NO3)3 / / NiNO3-based slurry comprises components in a weight ratio of 40 parts of FeCl3 or Fe(NO3)3 and 25 parts of NiCl or NiNO3;

[0093] Add 190 parts of water to FeCl3 / NiCl or Fe(NO3)3 / NiNO3 in the above raw materials according to the proportion of ingredients, wet ball mill for 6 hours, the ball mill speed is 50 rpm, after grinding, pass through a 300-mesh sieve and place in a drying oven to dry at 70°C for 5 hours, then add 25 parts of carboxymethyl cellulose and stir evenly, adjust to 35 degrees Baume, and prepare red mud-magnesium slag based slurry for standby use;

[0094] Step (2) soaking the corn cob in the slurry for 10 minutes, taking out and freeze-drying for 13 hours, and then putting it into a microwave reaction furnace preheated at 40° C. for 2 minutes, heating the temperature to 300° C. at a rate of 4° C. / min, keeping the temperature for 5 hours, and then cooling naturally to obtain a carbonized corn cob precursor with a porous wood structure, which is set aside;

[0095] Step (3) placing a graphite crucible in a sintering furnace, taking 80 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0096] The sintering furnace was heated from room temperature to 870°C at a heating rate of 14°C / min in a nitrogen atmosphere, then to 1700°C at a heating rate of 2°C / min, kept at that temperature for 4 h, cooled to 1050°C at a heating rate of 3°C / min, and kept at that temperature for 1.5 h.

[0097] Ferric chloride decomposes when heated at about 300°C (reaction 1) to form ferrous chloride and chlorine gas. Ferrous chloride cannot undergo reactions 3, 4, and 5 in the reduction reaction, resulting in a lack of Fe3Si shell and Fe and Ni metal precipitation on the surface of silicon carbide.

[0098] 2FeCl3=2FeCl2+Cl2↑ (Reaction 1)

[0099] Ferric nitrate decomposes at about 120°C. Although iron oxide is formed (reaction 2), a large amount of gas is formed at the same time, which destroys the structure infiltrated on the surface of the carbonized corn cob core and causes it to fall off, making it difficult to carry out reactions 3, 4, and 5 in subsequent reduction reactions. This also results in a lack of Fe3Si shell and Fe and Ni metal precipitation on the surface of silicon carbide.

[0100] 4Fe(NO3)3=heating 2Fe2O3+12NO2↑+3O2↑ (reaction 2)

[0101] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 3)

[0102] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 4)

[0103] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 5)

[0104] Comparative Example 4

[0105] Step (1) preparing a red mud-iron tailings-based slurry, wherein the raw materials of the red mud-iron tailings-based slurry include components in a weight ratio of: 45 parts of red mud and 30 parts of iron tailings;

[0106] The red mud and iron tailings in the above raw materials were added with 190 parts of water according to the proportion of ingredients, wet ball milled for 6 hours at a ball mill speed of 50 rpm, passed through a 300-mesh sieve after grinding, and placed in a drying oven at 70° C. for 5 hours, then 25 parts of carboxymethyl cellulose were added and stirred evenly, and adjusted to 35 degrees Baume to prepare a red mud-iron tailings based slurry for standby use;

[0107] Step (2) placing the corn cob cob in a microwave reactor preheated at 40° C. for 2 min, heating to 300° C. at a rate of 4° C. / min, keeping the temperature for 5 h, and then cooling naturally to obtain a carbonized corn cob cob precursor retaining a porous wood structure, then soaking the precursor in a red mud-iron tailings-based slurry for 10 min, taking it out and freeze-drying it for 13 h for later use;

[0108] Step (3) placing a graphite crucible in a sintering furnace, taking 80 parts of SiO and placing it at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover.

[0109] The sintering furnace was heated from room temperature to 870°C at a heating rate of 14°C / min in a nitrogen atmosphere, then to 1700°C at a heating rate of 2°C / min, kept at that temperature for 4 h, cooled to 1050°C at a rate of 3°C / min, kept at that temperature for 1.5 h, and then cooled to room temperature to obtain the target product.

[0110] The carbonized corn cob core is soaked in the slurry. Although a mineral coating is formed on its surface, due to the lack of microwave heating process, the surface mineral phase has a loose structure and does not form a strong bridge. During the freeze-drying process, the structure is easily destroyed due to the crystallization expansion of water molecules, resulting in a decrease in the integrity and total amount of the mineral coating. During the reduction reaction, the iron oxide reacts and forms gas, and the mineral coating structure is further destroyed and falls off, making it difficult to precipitate on the silicon carbide surface and undergo subsequent reactions 1, 2, and 3. Therefore, the target product Fe / Ni-SiC-Fe3Si wood structure absorbing material cannot be formed.

[0111] 3Fe2O3(s)+2SiO2(s)+13CO(s)→2Fe3Si(s)+13CO2(g) (Reaction 1)

[0112] 3Fe2O3(s)+2SiO(g)+11CO(g)→2Fe3Si(s)+11CO2(g) (Reaction 2)

[0113] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) (Reaction 3).

Claims

1. A method for preparing Fe / Ni-SiC-Fe3Si wood structure absorbing material using "industrial-agricultural" solid waste resources as raw materials, characterized in that: The steps include: Step (1), preparing a solid waste-based slurry; The raw material components of the solid waste-based slurry are as follows: 30-50 parts of red mud, 20-30 parts of any one or combination of iron tailings and magnesium slag; The raw materials are mixed by weight, 180-200 parts of water are added, wet ball milled for 5-6 hours, screened and dried after grinding, and then 20-30 parts of carboxymethyl cellulose are added and stirred evenly, and adjusted to 25-35 degrees Baume to prepare a solid waste-based slurry; Step (2), soaking the corn cob cob in the solid waste-based slurry for 5-10 minutes, taking it out for freeze-drying, and then putting it into a microwave reaction furnace, heating it to 280-320° C. at a rate of 3-5° C. / min, keeping it warm for 3-6 hours, and then cooling it naturally to obtain a carbonized corn cob cob precursor with a porous wood structure; Step (3), placing a graphite crucible in a sintering furnace, taking 50-100 parts of SiO and placing them at the bottom of the graphite crucible, placing a carbonized corn cob core precursor frame at the upper opening of the graphite crucible, and then covering the graphite crucible with a graphite cover, performing carbonization reaction and firing, and obtaining a wood structure absorbing material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the ball milling speed is 50 rpm; the ball milling product is dried by placing it in a drying oven at 60-70° C. for 3-5 hours.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (2), the freeze-drying time is 10-15 hours, and the microwave reaction furnace is preheated at 20-40° C. for 1-2 minutes before heating.

4. The preparation method according to claim 3, characterized in that: In the step (3), the specific heating process of the carbonization reaction firing is: from room temperature to 850-900°C at a heating rate of 13-15°C / min, then to 1500-1800°C at a heating rate of 1-3°C / min, keep warm for 3-5h, cool to 1000-1100°C at a rate of 2-4°C / min, keep warm for 1-1.5h, and then cool to room temperature.

5. The preparation method according to claim 4, characterized in that: In the step (3), the firing process is carried out under a nitrogen atmosphere.

6. A Fe / Ni-SiC-Fe3Si wood structure absorbing material prepared according to any one of the preparation methods of claims 1-5, characterized in that: The Fe / Ni-SiC-Fe3Si wood structure absorbing material is grey in color as a whole and has the original porous wood structure of a corn cob core.